Pemberdayaan Caregiver Keluarga Berbasis Online Dalam Perawatan Lansia Dengan Hipertensi Di Era Pandemi COVID 19: Online-Based Empowerment of Family Caregivers in Caring for Elderly People with Hypertension in the Era of the COVID 19 Pandemic - Margiyati, Margiyati; Wulan Sari, Novita (Chakra Brahmanda Lentera Institute, 2023)
The decreasing body immune of elderly people and the existence of hypertension comorbidity make the elderly people belong in high-risk group, thus they need to be paid special attention during the Covid-19 pandemic era. Some of the elderly people who had come to integrated healthcare center on monthly basis stopped the visits as well as the regular check-ups because they were afraid that they might had been infected with Covid-19. Based on the fact, there was a raising need to conduct an online-based dedicated community service which aimed at empowering the family as caregiver in treating elderly people with hypertension during Covid-19 pandemic era. The community service activity was carried out by observation/field visit, training via Zoom Meeting app, home visit assistance, and monitoring through BKL WhatsApp app. The subjects of the activity were 20 family caregiver taking care of elderly with hypertension who were registered at Setya Manunggal III Integrated Healthcare Center for Elderly People. The result of this community service activity showed that the level of caregiver’s knowledge in taking care of elderly raised, from lack of knowledge category 50%, adequate knowledge category 40%, and excellent knowledge category 10% to lack of knowledge category 0%, adequate knowledge category 40%, and excellent knowledge category 60%. After receiving training, there was an increase of 80% in caregiver’s skill, which was determined by their ability to provide the right diet, 60% of them were able to assist and accompany the elderly to do elderly exercise, and 90% of them were able to give therapy such as providing lemongrass water feet soak. Since there was a significant increase in knowledge and skill of the caregivers after conducting the training, so it is hoped that the caregivers are able to independently handle the proper treatments for elderly during Covid-19 pandemic era.